Salawat Kepada Nabi Dalam Persepektif Hadis - Qurrata A’yuni (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
Invoking blessing to the Prophet Muhammad is a command in Islam and is considered as a small prayer yielding big rewards. However, the current discourses of blessing invocation do not comply with the Islamic teaching taught by the prophet to his companions. Such invocation has various names and those who read it will get benefits. If the invocations were analyzed carefully one will find they contain blessings that should be submitted only to the Almighty Allah. Therefore, this article attempts to look for the answer of the main problems, what correct discourses of invocation taught by the Prophet PBUH and accordance with the Islamic teaching. There seven discourses of invocation considered as authentic. The main discourse is the discourse recited in the praying for the Prophet PBUH, his families, his wives, and heirs. The discourses of invocation to the Prophet enclose two prays, the invocation of blessing and benediction to the Prophet. The discourses taught by the Prophet do not contain the phrase sayyidina and no authentic hadith acknowledges it. Should this phrase be included in the jurisprudence, the Prophet PBUH has taught it in his lifetime.